Lichen sclerosus of the glans penis - Katarzyna Borowska; Piotr Brzeziński (Our Dermatology Online, 2022)
Lichen sclerosus (LS) is a chronic inflammatory skin disease of genital and extragenital skin. LS is associated with a potential for atrophy, destructive scarring, functional impairment, and malignant evolution. Spontaneous remissions are rare. Therefore, early diagnosis, prompt treatment, and long-term follow-up of affected patients are mandatory. We present a case of 53-year-old man with lichen sclerosus of the glans penis.